Power-Efficient Software. - SAXE, ERIC (Communications of the ACM, 2010)
The article discusses writing software that is efficient with respect to a system's power usage. Modern systems that involve multicore technology make more complex the task of efficiently managing resources. Resource management must take account of spatial or temporal considerations, or both. While efficient software will skillfully balance resource consumption and utilization, poorly written code introduces various inefficiencies including memory leaks and excessive creation of multiple threads.